Status of Utilizing Social Media Networks in the Teaching-Learning Process at Public Jordanian Universities - Muneera Abdalkareem Alshdefait; Mohammad . S. Alzboon (University of Science and Technology, Yemen, 2018)
This study aimed at finding out the status of utilizing social media networks in the teaching-learning process at public Jordanian Universities. To achieve the goal of the study, the descriptive developmental method was used and a questionnaire was developed, consisting of (35) statements. The questionnaire was checked for its validity and reliability. Then it was distributed to a sample of (382) male and female students from the undergraduate and graduate levels. The study results showed that the participants gave a low score to the status of utilizing social media networks in the teaching-learning process at public Jordanian universities. The results also showed that there were statistically significant differences between the participants of the study according to the academic rank attributed to the graduate students, and according to gender attributed to male students at the instrument macro level and on all dimensions of the two variables. In light of these results, the study recommended that public universities should utilize modern technology in the educational process, urge and encourage the teaching staff members to use the social media networks in the teaching-learning process and raise the students' awareness about the benefits of using social media networks. Keywords: Social media networks, Teaching-learning process, Public Jordanian Universities